Back to school after COVID-19 pandemic: Resumption or transitional disruption? - Mohammad Niaz Asadullah (Asian Development Bank Institute (ADBI), 2023)
Since its onset in 2020, the COVID-19 pandemic has globally disrupted school operations, leading to a shift to some form of homeschooling arrangements. After two years, in March 2022, the government of Malaysia officially reopened all schools, ending its homeschooling program. This relatively long-lasting shock to onsite schooling has impacted learners, parents, and teachers in multiple dimensions, creating additional challenges for a full learning recovery. As all countries have now reopened schools for students to return, it is important to learn from student experiences. In this paper, we exploit a purposefully designed, nationwide, cross-sectional survey of government-owned primary and secondary schools in Malaysia to document student learning experiences during the early months of the home-to-school transition. We do so in multiple dimensions using objective and subjective indicators, and we additionally ask how this transition was influenced by pretransition homeschooling experience. Our empirical analysis and choice of indicators is guided by a conceptual framework that distinguishes between two competing hypotheses related to school reopening experiences: resumption vs transitional disruption. We find that 59% of secondary and 72% of primary level students report that they are happy to be back in school. School reopening also coincides with a significant reduction in educational-related worries (e.g., concerns over dropout, learning loss, and loss of interest in study) and indices of negative emotions (i.e., feelings of being tense, depressed, and restless), particularly among secondary school students. More importantly, those satisfied upon return to school report a statistically significant reduction in worries related to learning loss. These correlations support the resumption hypothesis. Yet our data highlights an important puzzle: Even after school reopening, one-third of students report that they do not learn more, at least one-fifth report a struggle to catch up on studies, and up to 40% are concerned about learning loss. The majority of learners additionally report not receiving more support from teachers and parents. Recipients of public aid as well as private (i.e., parental) support report being happy about school reopening and are less likely to report "not learning more." We conclude by discussing these somewhat paradoxical findings and the need for remedial measures beyond financial support for struggling learners to minimize post school reopening, transitional disruptions.
Keywords: D10; I21; J22; Q50; 330; COVID-19; edtech; learning crisis; home-based education; school closure